(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1994)
Coccolithophorids collected from the euphotic zone in the Arabian Sea during the tail end of summer monsoon (Sept. 20 to Oct. 06, 1992) were studied. Nineteen species were recorded, most abundantm among them were, Emiliania huxleyi, Umbilicosphaera irregularis, Umbilicosphaera sibogae var. foliosa and Gephyrocapsa oceanica. Low fertility of water during September-October is believed to have caused the abundance of E. huxleyi and U. irregularis. It has also been observed that malformations of E. huxleyi are common during the summer monsoon upwelling period. It was also observed that the overall coccolirhophorid density decreases from south to north. Higher coccolithophorid densities in the subsurface depths are attributed to suspected blooms and thermocline depth.